KEKALAHAN PARTAI KOALISI MERAH PUTIH PADA PEMILU PRESIDEN DAN WAKIL PRESIDEN REPUBLIK INDONESIA TAHUN 2014 DI KECAMATAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI - Welliam Harvey; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In 1945 Article 6A Paragraph 2 Candidate Pair of President and Vice Presidentshall be nominated by a Political Party or a coalition of political parties prior to theGeneral Election General Election. In this case the electoral system is an importantfactor. Therefore, the authors intend to conduct research with the aim to explain thedefeat of the Coalition Party Red and White in the election of President and VicePresident of the Republic of Indonesia in 2014 in the district of the Land Army LogasRegency Kuantan Singingi and the factors that influence it.The location of this research is the District Land Army Logas Singingi RegencyKuantan. This study includes qualitative research, with data collection techniquesinterview, documentation, and research informants determined by purposive samplingtechnique. In this study, the theory used is derived from the theory proposed byNazuruddin Sjamsuddin, Zukifli Hamid, Personal Toto, H.Anto Djawamaku, and JamesBuchanan regarding the cause of divisions and conflicts within the political parties andcoalitions of parties. Results of this study concluded that the defeat of the CoalitionParty Red and White in the election of President and Vice President of the Republic ofIndonesia in 2014 in the district of the Land Army Logas Regency Kuantan Singingidue to a lack of coordination elite and elite coalition center coalition led to overlappingareas of interest between the central elite with elite area, lack of campaign funds,discriminatory policies and voters focused imaging media.Keywords: Presidential Election, The Coalition Red and White